2015
DOI: 10.1039/c5ra19775a
|View full text |Cite
|
Sign up to set email alerts
|

Nearly warm white-light emission of silicon-rich amorphous silicon carbide

Abstract: An amorphous Si-rich SiC film with nearly warm white-light photoluminescence is synthesized to serve as a solid-state phosphorous material for white-lighting applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…In the future, such a band-engineered a-SiC solid-state phosphor could easily nd its potential role in monolithically integrating with semiconductor light-emitting or laser devices for white-lighting applications. 47…”
Section: Resultsmentioning
confidence: 99%
“…In the future, such a band-engineered a-SiC solid-state phosphor could easily nd its potential role in monolithically integrating with semiconductor light-emitting or laser devices for white-lighting applications. 47…”
Section: Resultsmentioning
confidence: 99%
“…Tohmon et al claimed that the PL of NOV defects in oxygendeficient high-purity silica glass at 459 nm [80]. The blue PL for NOV defects not only in the Si- In contrast to SiO x , either SiN x or SiC x is also considered as host matrix to confine the Si-QDs [63][64][65][66][67][68][69][70][71][72][73][74][75][76]. In 1992, Chen et al utilized the PECVD and Ar + -laser annealing to fabricate the Si:H/SiN x :H multiple quantum well (MQW).…”
Section: Photoluminescence Of Si-qdmentioning
confidence: 99%
“…Huang et al changed the SiH 4 fluence from 0.5 to 8 sccm to suppress the C/Si composition ratio and increase the Si-QD size for blue-to-green shifting PL wavelength from 440 to 520 nm [72]. Tai et al further demonstrated the Si-rich SiC synthesis for obtaining red PL between 630 and 660 nm from Si-QDs and 480 nm for SiC-QDs [73,74].…”
Section: Photoluminescence Of Si-qdmentioning
confidence: 99%
See 1 more Smart Citation
“…White emitting nanomaterials are of current interest for use in organic light emitting diodes, pollution monitoring, and detection of ions . Sensors based on white emitting particles are expected to be more sensitive to analytes because white light is composed of three color components in specific intensity ratios, and any change in one color intensity can produce detectable, off‐white emission.…”
Section: Introductionmentioning
confidence: 99%